Proof-search in hybrid logic - Aleknavičiūtė, Daiva; Norgėla, Stanislovas (Lietuvos matematikos rinkinys, 2008)
This paper describes a new tactic for proof-search in Hybrid logic H(@), which always terminates.
Keywords: hybrid logic; sequent calculus